2020
DOI: 10.1101/2020.02.21.960245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA-dependent macromolecular condensation drives self-assembly of the meiotic DNA break machinery

Abstract: Formation of meiotic DNA double-strand breaks (DSBs) by Spo11is tightly regulated and tied to chromosome structure, but the higher-order assemblies that execute and control DNA breakage are poorly understood. We address this question through molecular characterization of Saccharomyces cerevisiae RMM proteins (Rec114, Mei4 and Mer2)-essential, conserved components of the DSB machinery. Each subcomplex of Rec114-Mei4 (2:1 heterotrimer) or Mer2 (homotetrameric coiled coil) is monodisperse in solution, but they in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…Furthemore, Spp1 associated with Mer2 has a longer residence time on nucleosomes when compared with Spp1 when part of COMPASS 15 residues 140-256 of Mer2 12,13 which we from now on refer to as Mer2 "core" ( Figure 1B). We measured the molecular mass of Mer2 core by size exclusion chromatography coupled to multi-angle light scattering (SEC-MALS) and concluded that the Mer2 core is a tetramer ( Figure 1D), consistent with recently published data 17 . We also find that while most Mer2 constructs lacking the core are monomeric, there is also a dimerisation region in the C-terminal region between residues 255 and 314 ( Figure 1D).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthemore, Spp1 associated with Mer2 has a longer residence time on nucleosomes when compared with Spp1 when part of COMPASS 15 residues 140-256 of Mer2 12,13 which we from now on refer to as Mer2 "core" ( Figure 1B). We measured the molecular mass of Mer2 core by size exclusion chromatography coupled to multi-angle light scattering (SEC-MALS) and concluded that the Mer2 core is a tetramer ( Figure 1D), consistent with recently published data 17 . We also find that while most Mer2 constructs lacking the core are monomeric, there is also a dimerisation region in the C-terminal region between residues 255 and 314 ( Figure 1D).…”
Section: Introductionsupporting
confidence: 89%
“…Presumably this is essential given that the interaction between COMPASS bound Spp1 and H3K4 me3 is transient, whereas the association of the DSB forming machinery is an apparently more stable event 15 . Given that the interaction domain is the same as the tetramerisation domain we speculate that the antiparallel arrangement of coiled-coils of Mer2 core form two mirrored binding sites for Spp1, with V195 at the centre 14,17 .…”
Section: Discussionmentioning
confidence: 98%
“…This strongly suggests that Spo11 complexes are tethered on a surface (Johnson et al, 2019). Based on the intrinsic property of Rec114-Mei4 and Mer2 to undergo DNA-driven macromolecular condensation (Claeys Bouuaert et al, 2020), we propose that this surface is composed of higher-order Rec114-Mei4-Mer2 nucleoprotein assemblies attached to the chromosome axis (Supplementary Figure 10B). This surface is therefore occupied by multiple Spo11 subunits that can simultaneously engage the DNA substrate.…”
Section: The Effect Of Spo11 Dna Binding On Dsb Processingmentioning
confidence: 90%
“…Model of assembly of the DSB machinery. DNA-driven condensation by Rec114-Mei4-Mer2 is proposed to provide a platform that recruits the core complex, where it engages its DNA substrate (Claeys Bouuaert et al, 2020). 'Biot' indicates the position of a 3'-biotin modification.…”
Section: Supplementary Figuresmentioning
confidence: 99%
“…In budding yeast, the Spo11 accessory proteins Rec114, Mei4, and Mer2 (RMM) bind stably to the chromosome axis as foci [73][74][75][76][77]. In the presence of DNA, RMM can phase-separate in vitro, and the resulting condensates can recruit Spo11 [78]. RMM mutants with reduced DNA-binding activity form fewer foci and fail to from double-strand breaks in vivo [78].…”
Section: Phase Separation During Meiotic Recombinationmentioning
confidence: 99%